OPTIMALISASI PENGELOLAAN UNIT COST FOOD DAN BEVERAGE UNTUK PROFITABILITAS BERKELANJUTAN HOTEL BERBINTANG DI YOGYAKARTA - Martono Widagdo, Yohanes (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyse the optimalisation strategy for unit cost management in the Food and Beverage (F&B) division in order to improve the sustainable profitability of star-rated hotels in Yogyakarta. In the hospitality industry, particularly in star-rated hotels, the F&B division contributes significantly to non-room revenue. However, high operational costs and fluctuations in raw material prices require management to exercise effective cost control without compromising service quality. Using a qualitative descriptive approach, this study examines cost unit management practices based on recipe standards, Point of Sales (POS) systems, selection of suppliers with competitive prices, and menu engineering strategies. In addition, technology integration and budgeting are also analysed as part of cost efficiency efforts. The results of the study indicate that the success of unit cost optimisation is determined by the synergy between operational efficiency, cash flow control, and innovation in the presentation of F&B products. The conclusion of this study emphasises that proper unit cost management not only impacts short-term profits, but also supports the long-term sustainability of the hotel business, especially amid dynamic markets and ever-changing consumer behaviour.